ANALISIS MINAT MASYARAKAT UNTUK INVESTASI EMAS DI PEGADAIAN - Ramadhan, Faessal Ilham; Aminullah Achmad Muttaqin (Contemporary Studies in Economic, Finance and Banking, 2024)
The purpose of this study is to assess the community's interest in gold investment through the services offered by Pegadaian Blitar and to understand the performance achievements of Pegadaian Blitar regarding its gold investment products. This research focuses on various factors that influence individuals to engage in gold investment activities at Pegadaian Blitar. Consequently, the researcher needs to conduct in-depth observations regarding the ongoing phenomena within the community itself. Employing a qualitative method, this study aims to gain a profound understanding of the phenomena occurring at Pegadaian. Findings from this research indicate that the Blitar community has an interest in gold investment at Pegadaian, facilitated by gold savings products that assist individuals in investing. The community is motivated to secure their future, and Pegadaian has been relatively successful in promoting its products. However, Pegadaian still needs to educate the community further about the importance of investment so that they become more interested in investing.